The Sex Identification of the Sun Conure (Aratinga solstitialis) Using Calamus Based on Polymerase Chain Reaction - Pinayungan, Probo Probo Warih Tatag; Aprinda Ratna Lovela; Eduardus Bimo Aksono; Ismudiono; Boedi Setiawan; Kadek Rachmawati; Jola Rahmahani (Universitas Airlangga, 2024)
Sex identification of Sun Conures (Aratinga solstitialis) is crucial for breeding and preservation, as well as increasing sun conure populations. These birds are sexually monomorphic. Therefore, Determination between male and female carried out by their morphology examination. The Polymerase Chain Reaction (PCR) method, utilizing molecular-based technology, was employed to determine the sex of Aratinga solstitialis in this study. The P2 and P8 primers were utilized in this method, which has been deemed suitable and accurate for sex identification through calamus samples. The research focused on two 28-month-old Aratinga solstitialis birds. Calamus samples were collected and subjected to PCR amplification using the extracted calamus. The resulting PCR products were then visualized using electrophoresis with a 1% agarose gel. In the electrophoresis photo, the presence of two bands indicated a female specimen, whereas a single band indicated a male specimen. The result of the gel electrophoresis research showed that both of the Aratinga solstitialis were male with one band of each bird on ranged from 300-400 base pairs. The result show that the Polymerase Chain Reaction method in terms for sex identification on monomorphic birds, especially Aratinga solstitialis birds is very effective to differentiate the sex of young birds and the adults.